A survey of detection techniques for sperm whale and dolphin echolocation clicks - Gracic, Mak; Gubnitsky, Guy; Diamant, Roee (Frontiers in Marine Science, 2025)
Echolocation clicks, emitted by Sperm Whales (Physeter macrocephalus) and Dolphins for foraging, echolocation and socialization, serve as bioindicators for monitoring marine ecosystems. Detecting click signals provides information on the abundance of species, their behavior and their responses to environmental changes. This paper provides a survey of the many detection and classification methodologies for clicks, ranging from 2002 to 2023. We divide the surveyed techniques into categories by their methodology. Specifically, feature analysis (e.g., phase, ICI and duration), frequency content, energy-based detection, supervised and unsupervised machine learning, template matching and adaptive detection approaches. Also surveyed are open access platforms for click detections, and databases openly available for testing. Details of the method applied for each paper are given along with advantages and limitations, and for each category we analyze the remaining challenges. The paper also includes a performance comparison for several schemes over a shared database. Finally, we provide tables summarizing the existing detection schemes in terms of challenges address, methods, detection and classification tools applied, features used and applications.